Response Surface Methodology for Removal of Cobalt from Aqua Solutions Using Nevsehir and Kayseri Pumice Adsorbents - Cicek, E. (Asian Journal of Chemistry, 2010)
The adsorption of cobalt ions from aqueous solutions onto Nevsehir and Kayseri pumice was investigated in this study. Pumice samples were activated at 873 K for 2 h before contact with cobalt ions. In order to develop the predictive regression models all experiments were performed according to statistical designs. The concentrations of cobalt ions were measured by UV-Vis spectrophotometer. The maximum removal efficiencies of 60 and 80 % have been obtained experimentally using Nevsehir pumice and Kayseri pumice, respectively. The goal of modeling was analyze the influence of sorbent dosage and initial cobalt concentration on sorption efficiency in case of Nevsehir and Kayseri pumice sorbent. The contour response surface plot was drawn for spatial presentation of regression equation. The experiments with radioactive 60Co were performed to test Kayseri pumice ability to remove radioactive compounds. The results showed that Nevsehir and Kayseri pumice can be used as efficient sorption materials for cobalt ions.